In-centre nocturnal haemodialysis: The experience of a centre - Mesquita,Isabel (2015)
Background and Objectives: As a result of improved clinical and quality-of-life outcomes, in-centre nocturnal haemodialysis emerges as one of the alternatives to conventional haemodialysis. Even today, little is known about the flow of patients through in-centre nocturnal haemodialysis programmes or about patients survival or technique failure. This study sought to address this gap in knowledge. Materials and Methods: Retrospective, descriptive study that included all patients in in-centre nocturnal haemodialysis programme, between January 1995 and December 2011, which involved 51 patients. Descriptive data at baseline were presented as means or percentages of the total. We used Kaplan-Meier survival curves for patient survival. Results: Patients underwent for more than 5.5 hours thrice weekly sessions and remained in the technique for a mean period of 59.5 ± 73 months. The annual input and output of patients in the programme was on average of to 2.1 and 2.5 patients, respectively. Forty-three patients discontinued the technique: kidney transplantation in 24, conventional haemodialysis in 11 and peritoneal dialysis in three patients, with mean times in in-centre nocturnal haemodialysis of 37.4 ± 46.4, 85.3 ± 93 and 59.7 ± 79.7 months, respectively. Throughout the period under review, five patients died (9.8%). Unadjusted survival at 20 years was 65% in patients who remained in in-centre nocturnal haemodialysis. Conclusion: In-centre nocturnal haemodialysis is associated with a higher survival rate, notwithstanding the possibility of selection bias resulting from patients profile that opts for this modality. The relative contribution of patient selection versus effect of therapy on outcomes requires evaluation in future prospective clinical trials